The Influence of the Teaching Campus Program as an Effort in Preparation to Become a Professional Lecturer in Students - Nababan, Juandi; Rajagukguk, Holmes (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to determine the influence of lecturer competency on English language education students at FKIP Sisingamangaraja XII Tapanuli University. The research method used is descriptive quantitative. Data collection was carried out using population, samples, and sampling techniques. All Class I, II, and III Teaching Campus participants from the 2018-2019 FKIP Sisingamangaraja XII Tapanuli University English Language Education study program are the population of this research. The sample for this research is all participants in the 2018-2019 FKIP Sisingamangaraja XII Tapanuli University English Language Education Teaching Campus program from classes I, II, and III, totaling 33 students. Data and data sources were obtained from lecturers and students of English Language Education, FKIP, Singsingarah XII Tapanuli University. In this research, the researcher's analysis to test this hypothesis uses a simple linear regression test to determine the influence of the independent variables on the respective dependent variables. The results of the research show that the influence of the Campus Teaching Program as an Effort in Preparing to Become a Professional Lecturer on English Language Education Students at FKIP Sisingamangaraja XII Tapanuli University is Adequate Academic Qualifications amounting to 90%, Experience in the Field amounting to 80%, Mastery of Teaching Materials amounting to 58%, Adaptation Ability amounting to 85%, Use of Educational Technology 75%, Coaching and Guidance amounting to 55%, Responsiveness to Students amounting to 95%, Evaluation and Feedback amounting to 65%, Ethics and Professional Attitudes 80%, and Innovation in Teaching amounting to 91%. There is a significant influence of the Independent Learning Campus Teaching Program (MBKM) as an effort to become competent lecturers for English language education students at FKIP Sisingamangaraja XII Tapanuli University with an average score of 80%.